Crowdfunding e innovación financiera: análisis de la regulación en materia de financiación colaborativa en Colombia (2020)
The regulation of the so-called financial innovation comes with certain challenges that must consider the promotion of models that comply with the protection of the financial system, and of the actors that intervene. However, it must also promote creativity and avoid becoming an obstacle to new ideas. Thus, crowdfunding schemes are an opportunity for financial innovation to gain importance within financial regulation and to seek a balance between protecting investors, promoting productive projects and promoting the platforms that connect both parties. To this extent, the mediation of financial services provided by Fintechs allows transaction costs to be low, and therefore, the commission charged by mediation is lower. Although, for the majority of the doctrine, there are two large crowdfunding models: financial and charitable, this research aims to develop its analysis in the financial model. In Colombia, Decree 1357 of 2018 was issued, and was modified by Decree 1235 of 2020, which for the first time regulates collaborative financing activities with financial returns in the country. Throughout this investigation, it is demonstrated that this regulation resulted in a series of obstacles for entities interested in implementing a crowdfunding platform in Colombia, due to the number of requirements necessary to operate legally. In this way, by pretending to demand the same requirements as any credit establishment in the financial system, it ends up distorting the very definition of collaborative financing and its quality as a fintech model, which from its origins has sought to solve the problems of small investors and MiPymes (micro, small and medium enterprises) as an alternative to traditional credit institutions belonging to the conventional financial system.